قضايا اجتماعية في ماليزيا من وجهة النظر الإسلامي : Social Issues in Malaysia from the Islamic Perspective - Farahanim binti Mohd Esa; Rahmah Binti Ahmad H. Osman; Norziyana binti Mohd Akhir; Afifah Toklubok (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص تتطرق هذه الدراسة إلى مناقشة القضايا الاجتماعية التي وقعت في ماليزيا من وجهة النظر الإسلامي. وقد نهجت هذه الدراسة المنهج الوصفي التحليلي من خلال استقراء القضايا المتعلقة بالمجتمع الماليزي في المراجع والمصادر المتوفرة لدى الباحثات ووصفها، وأيضا تحليلها من المواقف الغربية والماليزية والإسلامية. وستتناول هذه الدراسة المحاور الآتية: القضايا الثقافية مثل التوجه الجنسي، والهوية الجنسية؛ والقضايا الأخلاقية مثل حرية التعبير، والاختلاط بين الجنسين والخلوة بين غير المتزوجين؛ والقضايا الأسرية مثل تطور أدوار الزوجين، وتربية الأولاد أثناء الوباء. وهدفت هذه الدراسة إلى تسليط الضوء على هذه القضايا المختارة من المنظور الإسلامي وكذلك إعطاء الآراء المبررة عند العلماء والباحثين فيها. ومن ثم، توصلت هذه الدراسة إلى النتائج المهمة من أبرزها: الكشف عن آراء العلماء والخبراء واستكشاف مواقفهم الإسلامية تجاه مقاربة ماليزيا على التعامل مع هذه القضايا الاجتماعية. Abstract This study discusses the social issues that occurred in Malaysia from the Islamic point of view. This study has taken the descriptive analytical approach by describing issues related to the Malaysian society in the references and sources available to the researchers, as well as analysing them from Western, Malaysian and Islamic attitudes. This study will address the following topics: cultural issues such as sexual orientation and gender identity; ethical issues such as freedom of expression, mixing of the sexes and intimacy among the unmarried; and family issues such as developing the roles of spouses and children’s education during the epidemic. This study also aimed to shed light on these selected issues from the Islamic perspective, as well as to give justified opinions of scholars and researchers in them. Thus, this study reached important results and the most significant of which is: revealing the opinions of scholars and experts and exploring their Islamic attitudes towards Malaysia’s approach to dealing with these social issues.